2022
DOI: 10.1021/acs.est.2c02612
|View full text |Cite
|
Sign up to set email alerts
|

The Unique CO Activation Effects for Boosting NH3 Selective Catalytic Oxidation over CuOx–CeO2

Abstract: Slip NH3 is a priority pollutant of concern to be removed in various flue gases with NO x and CO after denitrification using NH3-SCR or NH3-SNCR, and the simultaneous catalytic removal of NH3 and CO has become one of the new topics in the deep treatment of such flue gases. Synergistic catalytic oxidation of CO and NH3 appears to be a promising method but still has many challenges. Due to the competition for active oxidizing species, CO was supposed to hinder the NH3 selective catalytic oxidation (NH3-SCO). Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…This illustrated that for R/Z, the ammonia adsorption on the Lewis acid site was more stable than on the Bro̷nsted acid site. Note that a new peak of amide (−NH 2 ) appeared at 1568 cm –1 starting from 100 °C. , At the same time, the peak at 1265 cm –1 was red-shifted and a peak associated with −NH 2 also appeared at 1250 cm –1 . , The intensity of these peaks progressively increased in 100–200 °C and subsequently decreased after 200 °C. This might be due to the activation of NH 3 species adsorbed on Lewis and Bro̷nsted acid sites below 200 °C, which dissociates H and thus generated −NH 2 intermediate species (eq ).…”
Section: Resultsmentioning
confidence: 96%
“…This illustrated that for R/Z, the ammonia adsorption on the Lewis acid site was more stable than on the Bro̷nsted acid site. Note that a new peak of amide (−NH 2 ) appeared at 1568 cm –1 starting from 100 °C. , At the same time, the peak at 1265 cm –1 was red-shifted and a peak associated with −NH 2 also appeared at 1250 cm –1 . , The intensity of these peaks progressively increased in 100–200 °C and subsequently decreased after 200 °C. This might be due to the activation of NH 3 species adsorbed on Lewis and Bro̷nsted acid sites below 200 °C, which dissociates H and thus generated −NH 2 intermediate species (eq ).…”
Section: Resultsmentioning
confidence: 96%
“…The fitting accuracy could be testified by the R factor (0.0103). The Cu 2p XPS spectra (Figure S4b) indicated that the Cu species on the surface of the PdCu 1.2 /Al 2 O 3 catalyst all existed in the Cu 2+ state, considering that the binding energy centered at 953.8 and 933.7 eV attributed to the 2p 1/2 and 2p 3/2 of Cu 2+ species and the characteristic satellite peak at 939–946 eV. , From the Cu K-edge XANES spectra (Figure d), the absorption edge of PdCu 1.2 /Al 2 O 3 was very close to that of CuO. The Cu–O and Cu–Cu bonds were quite similar to those in the CuO standard sample in Figure e (the curve fit is demonstrated in Figure S6, and EXAFS fitting parameters are shown in Table S4), further proving the existence of CuO in PdCu 1.2 /Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The activity of Cu/NCNT also outperformed those Cu catalysts (with the same nominal Cu loading of ca. 2 wt %) supported on other types of carbons, namely, pristine CNTs (p-CNT) and AC, or non-carbon materials (ZSM-5 and Al 2 O 3 ) at temperatures in the 160–220 °C range (Figure b), and it is among the most active Cu-based NH 3 -SCO catalysts reported in the open literature (Table S2) in terms of T 50 , i.e., the temperature to achieve 50% conversion of NH 3 . , Notably, Cu/CNT catalysts (even the relatively low-performance Cu/p-CNT sample) demonstrated clearly lower T 50 values than those Cu catalysts on non-CNTs materials, highlighting the superiority of CNT supports in NH 3 -SCO catalysis. In addition, the NH 3 -SCO activity of Cu/NCNT can be sustained without noticeable degradation even after degreening treatment at high reaction temperatures, i.e., at 220 °C for 8 h and then 300 °C for 8 h (Figure S2a).…”
Section: Resultsmentioning
confidence: 99%